A Comparison of Home Health Utilization, Outcomes, and Cost Between Medicare Advantage and Traditional Medicare. Issue 1 (January 2022) - Casebeer, Adrianne W.; Ronning, David; Schwartz, Richard; Long, Charron; Bhattacharya, Rituparna; Uribe, Claudia; Brown, Courtney R.; Cameron, Joy; Painter, Phil; Sharma, Anup; Spitale, Sandy; Powers, Brian; et al.
Abstract : Background: Home health use is rising rapidly in the United States as the population ages, the prevalence of chronic disease increases, and older Americans express their desire to age at home. Enrollment in Medicare Advantage (MA) plans rather than Traditional Medicare (TM) has grown as well, from 13% of total Medicare enrollment in 2004 to 39% in 2020. Despite these shifts, little is known about outcomes and costs following home health in MA as compared with TM. Objective: The objective of this study was to measure the association of MA enrollment with outcomes and costs for patients using home health. Design: This was a retrospective cohort study. Participants: Patients enrolled in plans offered by 1 large, national MA organization and patients enrolled in TM, with at least 1 home health visit between January 1, 2017, and June 30, 2018. Exposure: MA enrollment. Main Measures: We compared the intensity of home health services and types of care delivered. The main outcome measures were hospitalization, the proportion of days in the home, and total allowed costs during the 180-day period following the first qualifying home health visit during the study period. Key Results: Among patients who used home health, our models demonstrated enrollment in MA was associated with 14%, and 6% decreased odds of 60- and 180-day hospitalization, respectively, a 12.8% and 14.7% decrease in medical costs exclusive and inclusive of home health costs, respectively, and a 0.27% increase in the proportion of days at home during the 180-day follow-up, equivalent to an additional half-day at home. There were few differences in home health care delivered for MA and TM [mean number of visits in the first episode of care (17.1 vs. 17.3) and mean visits per week (3.2 vs. 3.3)]. The mean number of visits by visit type and percent of patients with each type was similar between MA and TM as well. Conclusions: Compared with enrollment in TM, enrollment in MA was associated with improved patient-centered outcomes and lower cost and utilization, despite few differences in the way home health was delivered. These findings might be explained by structural components of MA that encourage better care management, but further investigation is needed to clarify the mechanisms by which MA enrollment may lead to higher value home health care. Abstract : Supplemental Digital Content is available in the text.